Application of Cognitive Defusion Group Counselling to Reduce Insecurity among Junior High School Students - Mimi Hasmiati; Bau Ratu; Azam Arifyadi; Hasan Hasan (MASI Mandiri Edukasi, 2025)
This study aims to examine the effectiveness of Cognitive Defusion group counselling services in reducing students' levels of insecurity. The study employed a Guidance and Counselling Action (PTBK) design, which was conducted in two cycles with eight eighth-grade students serving as research subjects, selected through purposive sampling. Data were collected through questionnaires and interviews, and then analysed both descriptively and quantitatively. The results showed a significant decrease in insecurity levels, from 77.12% (high category) in the pre-cycle to 61% (medium category) in cycle I, and further decreased to 55.5% (low category) in cycle II. These findings suggest that the Cognitive Defusion technique is effective in helping students release negative thoughts, boost self-confidence, and enhance self-acceptance.